Synergetic utilization of copper slag and ferruginous manganese ore via co-reduction followed by magnetic separation process. (20th March 2020) - Zhu, Deqing; Xu, Jiwei; Guo, Zhengqi; Pan, Jian; Li, Siwei; Pan, Liaoting; Yang, Congcong
Abstract: Attempts to economically and effectively treat copper slag (CS) and ferruginous manganese ore(FMO) using the traditional direct reduction–magnetic separation process have faced many challenges, such as low levels of metal recovery, poor cost-effectiveness and the need for a high proportion of additives. This paper proposes an eco-friendly process to synchronously utilise copper slag and ferruginous manganese ore by co-reduction followed by a magnetic-separation process to solve those problems. In the process, MnO2 within FMO acted as a catalyst to promote the reduction of fayalite and copper sulphide contained in CS, and thus improve the metallisation rate of Fe and Cu. Meanwhile, CS, possessing the low melting point, can enables more liquid phase generation and improve the growth of alloy particle, which is beneficial for the full liberation of Fe–Cu alloy. Under the optimum conditions, A crude Fe–Cu alloy powder containing 88.83% Fe and 1.07% Cu was prepared, which can be used in an electronic furnace to produce Cu-bearing steels. A high recovery of 85.89% Fe and 87.74% Cu can be obtained using this process, thereby confirming its efficiency. Additionally, Mn contained in the ferromanganese ore was enriched into the magnetic tailing in the form of low-valence manganese (II) oxides, which can be easily extracted by acid leaching. Moreover, the mechanism involved in the co-reduction of CS and FMO was investigated by XRD, SHTT and SEM-EDS techniques, which further confirmed the complementary advantages about an organic integration of CS and FMO can realise the efficient beneficiation of the valuable metals from them. Graphical abstract: Image 1070 Highlights: Iron and copper within CS and FMO were beneficiated efficiently by the new process. The MnO2 in FMO was employed as a catalyst to promote reduction of fayalite and copper sulfide in CS. Synergistic reaction mechanism of CS and FMO in reduction process was revealed.